2022
DOI: 10.3390/plants11212845
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Biogenic Amines of Two Table Grapes (cv. Bronx Seedless and Italia) during Berry Development and Ripening

Abstract: Bronx Seedless and Italia (Vitis vinifera L.) are a variety preferred by consumers owing to their exciting flavour and widely cultivated in Aegean Region in Turkey. The aim was to identify the biogenic amines of these table grapes during berry ripeness. The biogenic amines were analyzed by HPLC in six different berry phenological stages. Italia grapes presented lower biogenic amine content than Bronx Seedless table grapes. The concentration of most of the biogenic amines analyzed linearly raised from the begin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Incesu et al (2022) studied the accumulation of biogenic amines in two varieties of grape berries during ripening. Although a difference in biogenic amine concentration between the varieties was observed, there was a consistent increase in concentration throughout the ripening process [13]. The concentration of most of the biogenic amines analyzed increased linearly from the beginning of berry touch to when the berries ripened during the harvesting stage.…”
Section: Changes In the Biogenic Amines Of Two Table Grapes (Cv Bronx...mentioning
confidence: 78%
“…Incesu et al (2022) studied the accumulation of biogenic amines in two varieties of grape berries during ripening. Although a difference in biogenic amine concentration between the varieties was observed, there was a consistent increase in concentration throughout the ripening process [13]. The concentration of most of the biogenic amines analyzed increased linearly from the beginning of berry touch to when the berries ripened during the harvesting stage.…”
Section: Changes In the Biogenic Amines Of Two Table Grapes (Cv Bronx...mentioning
confidence: 78%
“…The serotonin content recorded in grape pomace was in agreement with a previous study, which reported levels of this compound ranging from 0.085 to 0.242 µg/kg in various cultivars of sweet cherries [ 34 ]. In grapes, mean concentrations of serotonin ranging from below the method’s detection limit (<LOD) up to 2.28 µg/L in the indoleamine extract have been reported [ 35 ]. Furthermore, Murch et al described its erratic presence in part of the grapes analysed (30–35%), where concentrations up to 10.000 µg/kg were observed [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…They have gained attention for their potential health benefits such as antioxidant properties [6]. Table grapes, namely the 'Italia' and 'Bronx Seedless' cultivars, have gained prominence not only for their exquisite taste [7], but also for their abundant phytochemical content, which encompasses phenolic acids, C 13 -Norisoprenoids; phytoalexins, and flavonoids. These bioactive compounds are not only responsible for the remarkable visual and gustatory appeal of grapes but have also garnered significant attention for their potential health benefits, making grapes a subject of great interest for both the health sciences and agriculture [8].…”
Section: Introductionmentioning
confidence: 99%
“…Research have noted the potential of resveratrol in conferring cardiovascular benefits, as well as its anti-inflammatory and antioxidant properties [11]. Although the health benefits of these compounds are well-documented, understanding the variation in the phytochemicals of grapes across different berry development stages is essential for several reasons [7]. The specific mix of phytochemicals in grapes may vary considerably owing to factors namely grape cultivar, environmental conditions, cultural treatments, and maturation stage [12].…”
Section: Introductionmentioning
confidence: 99%